2009
DOI: 10.1021/om900404c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Study of Syn−Anti Isomerization of Nickel Complexes Bearing Amino-Linked N-Heterocyclic Carbene Ligands: The Effect of the Pendant Arm of the NHC

Abstract: The mono-(2) and bis(amino-NHC) (3) nickel halide complexes can be prepared in moderate yield by reacting Ni(PPh 3 ) 2 X 2 with the amino pendant linked NHC 1, [C{(MES)N(CHCH)-N(CH 2 CH 2 NHtBu)}], or its lithium bromide carbene adduct 1-LiBr. The mono(amino-carbene) nickel complexes (2) are paramagnetic species bearing a tetrahedrally distorted Ni center featuring a bidentate coordination mode via NHC and amine dative bonds. In contrast, the bis(amino-carbene) nickel complexes (3) are proton NMR active, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…In support of this rationale, we calculated the steric buried volume based on a known bidentate structure from our previous work, the amino-NHC nickel(II) complex 5. [14] Indeed, a bidentate feature in amino-NHCs generates a large buried volume of 48.1 %, thus making a compelling case for sterically controlled selectivity. Furthermore, the theoretical findings on cobalt-mediated hydroarylation of styrenes by Fu's group further support our observation of ligandcontrolled regioselectivity based on steric effects.…”
Section: Steric Influence On Linear Selectivitymentioning
confidence: 99%
“…In support of this rationale, we calculated the steric buried volume based on a known bidentate structure from our previous work, the amino-NHC nickel(II) complex 5. [14] Indeed, a bidentate feature in amino-NHCs generates a large buried volume of 48.1 %, thus making a compelling case for sterically controlled selectivity. Furthermore, the theoretical findings on cobalt-mediated hydroarylation of styrenes by Fu's group further support our observation of ligandcontrolled regioselectivity based on steric effects.…”
Section: Steric Influence On Linear Selectivitymentioning
confidence: 99%
“…This indicates that the Ni‐NHC bond undergoes proteolysis following oxidation. A second set of signals is observed that match to the known bis‐NHC complex NiCl 2 ( 1 a ) 2 that is formed in ca. 10 % yield.…”
Section: Resultsmentioning
confidence: 65%
“…The facile dynamic processes of 2 a are in sharp contrast to NiCl(allyl)(IMes) that contains a rigorously monodentate NHC and exhibits static allyl resonances at room temperature . We ascribe the greater fluxionality found in 2 a to the known, hemilabile character of the NHC 1 a . Reversible coordination of the secondary amine may have the further consequence of inducing allyl isomerization (Scheme ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The short intermolecular contact in 5a was a consequence of a possible electrostatic interaction between the hydrogen atom and the lone pair on the carbene carbon of another molecule. On the other hand, the steric influence imposed by the tert ‐butyl amino side‐arm in 5b diminished the intermolecular interaction, which was somewhat longer than in 5a (2.507 Å, 3.404 Å, 170°) 5e. Based on the above observation, we speculated that the intermolecular interactions in 5a would disrupt the stability of the amino–NHC.…”
Section: Resultsmentioning
confidence: 85%